Polarization plate with phase difference layer and image display device
By optimizing the structure of the polarized plate, including a bending layer made of liquid crystal composite materials and a pressure-sensitive adhesive layer, the problem of difficult to achieve thinning and high bending performance of the polarized plate in the prior art is solved, and the extreme thinning and excellent bending performance of the polarized plate are achieved, and it is suitable for display devices with various curvatures or foldables.
Patent Information
- Application Number
- JP2025008582
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-10
AI Technical Summary
It is difficult to develop a thin polarized plate with excellent bending performance for thin, curvature or foldable display devices.
A polarized plate structure is adopted including a polarizer, a protective layer, a bending layer and a pressure-sensitive adhesive layer. The bending layer is made of a liquid crystal composite material. By optimizing the thickness of the polarized plate and the puncture resistance strength of the protective layer, the bending index is improved, thereby achieving thinning and high bending performance of the polarized plate.
The extreme thinning and excellent bending performance of the polarized plate are achieved, and defects such as glue layer bubbles and polarizer cracks are avoided in rigorous bending tests. It is suitable for display equipment with curvature or foldable.
Smart Images

Figure 2025061550000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a retardation layer-attached polarizing plate and an image display device. [Background technology]
[0002] In recent years, image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (for example, organic EL display devices and inorganic EL display devices), have rapidly become widespread. In image display devices, a polarizing plate and a retardation plate are typically used. In practice, a retardation layer-attached polarizing plate in which a polarizing plate, a retardation plate, and a pressure-sensitive adhesive layer are integrated is widely used (for example, Patent Document 1). Recently, as the demand for thinner image display devices has increased, the demand for thinner retardation layer-attached polarizing plates has also increased. In addition, in recent years, there has been an increasing demand for curved image display devices and / or bendable or foldable image display devices. Therefore, there is a strong demand for a retardation layer-attached polarizing plate that is thin and has excellent foldability and can be applied to such image display devices. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 3325560 Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention has been made to solve the above-mentioned problems in the prior art, and a main object of the present invention is to provide a retardation layer-attached polarizing plate which is thin and has excellent foldability. [Means for solving the problem]
[0005] The polarizing plate with a retardation layer of the present invention comprises a polarizing plate including a polarizer and a protective layer at least on the viewing side of the polarizer; a retardation layer having a circular polarization function or an elliptically polarizing function and provided on the side opposite to the viewing side of the polarizing plate; and a pressure-sensitive adhesive layer provided on the side opposite to the polarizing plate of the retardation layer. WP is 0.06 mm or less, and the bending index, expressed by the following formula, is 150 or more: Flex index = puncture strength of protective layer on visible side (kgf / mm) / T WP (mm). In one embodiment, the polarizer has a thickness of 8 μm or less. In one embodiment, the retardation layer has a first retardation layer and a second retardation layer; the first retardation layer has Re(550) of 200 nm to 300 nm, and the angle between the slow axis and the absorption axis of the polarizer is 10° to 20°; the second retardation layer has Re(550) of 100 nm to 190 nm, and the angle between the slow axis and the absorption axis of the polarizer is 70° to 80°. In one embodiment, the first retardation layer and the second retardation layer are each an alignment solidified layer of a liquid crystal compound. In one embodiment, the thickness of the first retardation layer and the second retardation layer is each 2.5 μm or less. In one embodiment, the retardation layer is a single layer, the retardation layer has Re(550) of 100 nm to 190 nm, Re(450) / Re(550) of 0.8 to 0.95, and the angle between the slow axis and the absorption axis of the polarizer is 40° to 50°. In one embodiment, the viewer-side protective layer is made of a triacetyl cellulose film or a (meth)acrylic resin film. According to another aspect of the present invention, there is provided an image display device, the image display device including the above-mentioned retardation layer-attached polarizing plate. In one embodiment, the image display device is an organic electroluminescence display device. Effect of the Invention
[0006] According to an embodiment of the present invention, in a polarizing plate with a retardation layer, by optimizing the bending index by adjusting the thickness excluding the adhesive layer and the piercing strength of the viewing-side protective layer, a polarizing plate with a retardation layer that is thin and has excellent foldability can be realized. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0010] A. Overall structure of the polarizing plate with a retardation layer FIG. 1 is a schematic cross-sectional view of a polarizing plate with a retardation layer according to one embodiment of the present invention. The polarizing plate with a retardation layer 100 in the illustrated example typically has a polarizing plate 10 and a retardation layer in this order from the viewing side. In the illustrated example, the retardation layer has a first retardation layer 21 and a second retardation layer 22. The polarizing plate 10 includes a polarizer 11 and a protective layer 12 on the viewing side of the polarizer 11. Depending on the purpose, another protective layer 13 may be provided on the opposite side to the viewing side of the polarizer 11 (note that in the embodiment of the present invention, the another protective layer 13 may be preferably omitted). The first retardation layer 21 is bonded to the opposite side to the viewing side of the polarizing plate 10 via a first adhesive layer 31. The second retardation layer 22 is bonded to the opposite side to the viewing side of the first retardation layer 21 via a second adhesive layer 32. An adhesive layer 40 is provided as the outermost layer on the side opposite to the viewing side of the retardation layer (the side opposite to the first retardation layer 21 of the second retardation layer 22 in the illustrated example), so that the retardation layer-attached polarizing plate can be attached to an image display cell. For practical purposes, a separator (not shown) is temporarily attached to the surface of the adhesive layer 40 in a peelable manner. By temporarily attaching the separator, the adhesive layer is protected and the retardation layer-attached polarizing plate can be formed into a roll.
[0011] The first retardation layer 21 and the second retardation layer 22 are typically aligned and solidified layers of liquid crystal compounds. By using a liquid crystal compound, the difference between nx and ny of the resulting retardation layer can be significantly increased compared to non-liquid crystal materials, so that the thickness of the retardation layer for obtaining a desired in-plane retardation can be significantly reduced. As a result, a polarizing plate with a retardation layer can be significantly thinned. In this specification, the term "alignment solidified layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction within the layer and the alignment state is fixed. The term "alignment solidified layer" is a concept that includes an alignment hardened layer obtained by hardening a liquid crystal monomer as described later. In the first retardation layer 21 and the second retardation layer 22, typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the first retardation layer or the second retardation layer (homogeneous alignment). Typically, either the first retardation layer 21 or the second retardation layer 22 can function as a λ / 2 plate, and the other can function as a λ / 4 plate. For example, when the first retardation layer 21 can function as a λ / 2 plate and the second retardation layer 22 can function as a λ / 4 plate, the Re(550) of the first retardation layer 21 is preferably 200 nm to 300 nm, and the angle between its slow axis and the absorption axis of the polarizer 10 is preferably 10° to 20°; the Re(550) of the second retardation layer 22 is preferably 100 nm to 190 nm, and the angle between its slow axis and the absorption axis of the polarizer 10 is preferably 70° to 80°.
[0012] In another embodiment, the retardation layer may be a single layer (not shown). In this case, the retardation layer typically exhibits inverse dispersion wavelength characteristics and can function as a λ / 4 plate. Specifically, Re(550) of the retardation layer is preferably 100 nm to 190 nm, Re(450) / Re(550) is preferably 0.8 to 0.95, and the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°. Furthermore, in this case, preferably, another retardation layer (so-called positive C plate) whose refractive index characteristics show the relationship nz>nx=ny may be provided on the opposite side of the retardation layer from the polarizer.
[0013] In the embodiment of the present invention, the thickness T from the viewing side protective layer to the retardation layer (the second retardation layer in the illustrated example) WP is 0.06 mm (60 μm) or less, preferably 0.05 mm (50 μm) or less, more preferably 0.045 mm (45 μm) or less, and even more preferably 0.04 mm (40 μm) or less. WP The lower limit of the thickness T may be, for example, 0.03 mm (30 μm). WP If the thickness T is within this range, the bending rigidity of the retardation layer-attached polarizing plate (the force required to bend the retardation layer-attached polarizing plate) can be reduced, and therefore the bending stress applied to each component of the retardation layer-attached polarizing plate can be reduced. WP By optimizing the bending index by adjusting the piercing strength of the viewing-side protective layer described later in combination, it is possible to realize excellent bending properties (flexibility). Specifically, it is possible to realize a retardation layer-attached polarizing plate that does not cause defects in appearance such as air bubbles in the adhesive layer and cracks in the polarizer even in a severe bending test. When such a retardation layer-attached polarizing plate is applied to a bendable or foldable image display device (for example, an organic EL display device), it is possible to suppress defects in appearance such as air bubbles in the adhesive layer and cracks in the polarizer. In other words, it is possible to realize an image display device that is excellent in bending durability.
[0014] In an embodiment of the invention, the tortuosity index, expressed as: Flex index = puncture strength of protective layer on visible side (kgf / mm) / T WP (mm). The bending index is preferably 160 or more, more preferably 165 or more. The upper limit of the bending index can be, for example, 200. When the bending index is in such a range, excellent foldability can be realized. Specifically, a retardation layer-attached polarizing plate that does not cause appearance defects such as air bubbles in the adhesive layer and cracks in the polarizer even in a severe bending test can be realized. When such a retardation layer-attached polarizing plate is applied to a bendable or foldable image display device (for example, an organic EL display device), appearance defects such as air bubbles in the adhesive layer and cracks in the polarizer can be suppressed. In other words, an image display device with excellent bending durability can be realized. As is clear from the above formula, the bending index is a function of the thickness T WP and the piercing strength of the viewer-side protective layer. The technical significance of adjusting the piercing strength of the viewer-side protective layer so as to obtain the desired bending index is as follows. The piercing strength of the film can correspond to the repulsive force (strength) of the film against external stress when folded. Therefore, by typically setting the piercing strength of the outermost layer (the viewer-side protective layer in the case of a polarizing plate with a retardation layer) which is the point of action when folded to a predetermined value or more, the repulsive force of the viewer-side protective layer against external stress can be increased. As a result, the curvature of the folded portion becomes gentle, and the compressive stress can be dispersed. By dispersing the compressive stress (thus, by substantially reducing the compressive stress), the adverse effects on the adhesive layer and polarizer on the inside when folded can be reduced, and appearance defects such as air bubbles in the adhesive layer and cracks in the polarizer can be suppressed. In this way, the thickness T WP By optimizing the bending index by adjusting the piercing strength of the viewing-side protective layer in combination, the bending stress and compressive stress when the retardation layer-attached polarizing plate is folded (flexed) can be synergistically reduced, and as a result, excellent folding (flexibility) can be realized. Note that even if the elastic modulus (Young's modulus) of the viewing-side protective layer is adjusted, it is practically difficult to obtain a comprehensive index (configuration) that can realize excellent folding. This is because the elastic modulus often indicates a characteristic related to tension, and is therefore not suitable as a requirement for controlling folding.
[0015] The puncture strength of the visible side protective layer is WP may be any appropriate value that can realize the predetermined bending index when the predetermined range is satisfied. The piercing strength of the viewer-side protective layer is preferably 4.5 kgf / mm to 12 kgf / mm, more preferably 5 kgf / mm to 10 kgf / mm, and further preferably 5.5 kgf / mm to 8 kgf / mm. The piercing strength indicates the crack resistance when a film (here, the film constituting the viewer-side protective layer) is pierced with a predetermined strength. The piercing strength can be expressed, for example, as the strength at which the film breaks when a predetermined needle is attached to a compression tester and the needle is pierced into the film at a predetermined speed. The piercing strength can be adjusted by appropriately combining the constituent material of the film, the surface treatment of the film, and the like.
[0016] The total thickness of the retardation layer-attached polarizing plate (thickness from the viewing side protective layer to the adhesive layer) is preferably 80 μm or less, more preferably 70 μm or less, even more preferably 65 μm or less, and particularly preferably 60 μm or less. The lower limit of the total thickness may be, for example, 42 μm. A retardation layer-attached polarizing plate having such a total thickness can have extremely excellent flexibility and foldability due to a synergistic effect with the effect of optimizing the bending index. As a result, the retardation layer-attached polarizing plate can be particularly suitably applied to a curved image display device and / or a bendable or foldable image display device.
[0017] The retardation layer-attached polarizing plate may further include other optical functional layers. The type, characteristics, number, combination, arrangement position, etc. of the optical functional layers that can be provided in the retardation layer-attached polarizing plate may be appropriately set according to the purpose. For example, the retardation layer-attached polarizing plate may further have a conductive layer or a conductive layer-attached isotropic substrate (both are not shown). The conductive layer or the conductive layer-attached isotropic substrate is typically provided on the outside of the second retardation layer 22 (opposite side to the polarizing plate 10). The conductive layer or the conductive layer-attached isotropic substrate is typically an arbitrary layer that is provided as necessary, and may be omitted. In addition, when the conductive layer or the conductive layer-attached isotropic substrate is provided, the retardation layer-attached polarizing plate may be applied to a so-called inner touch panel type input display device in which a touch sensor is incorporated between an image display cell (for example, an organic EL cell) and a polarizing plate. In addition, for example, the retardation layer-attached polarizing plate may further include other retardation layers. Other optical characteristics (for example, refractive index characteristics, in-plane retardation, Nz coefficient, photoelastic coefficient), thickness, arrangement position, and the like of the retardation layer can be appropriately set depending on the purpose.
[0018] The above embodiments may be combined as appropriate, modifications that are obvious to those skilled in the art may be made to the components in the above embodiments, and the configurations in the above embodiments may be replaced with optically equivalent configurations.
[0019] The polarizing plate with a retardation layer may be in the form of a sheet or a long sheet. In this specification, the term "long sheet" means a long and narrow shape whose length is sufficiently longer than its width, and includes, for example, a long and narrow shape whose length is 10 times or more, preferably 20 times or more, than its width. The long polarizing plate with a retardation layer can be wound into a roll.
[0020] The components of the retardation layer-attached polarizing plate will be described in more detail below.
[0021] B. Polarizing plate B-1.Polarizer Any appropriate polarizer can be adopted as the polarizer 11. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0022] Specific examples of polarizers made of a single-layer resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene-vinyl acetate copolymer films that have been dyed with iodine or a dichroic substance such as a dichroic dye and stretched, and polyene-based oriented films such as dehydrated PVA films and dehydrochlorinated polyvinyl chloride films. A polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it is preferably used because of its excellent optical properties.
[0023] The dyeing with iodine is carried out, for example, by immersing the PVA-based film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment, or may be carried out while dyeing. Alternatively, the film may be stretched and then dyed. If necessary, the PVA-based film may be subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based film in water and washing it with water before dyeing, it is possible to wash off dirt and antiblocking agents on the surface of the PVA-based film, and also to swell the PVA-based film and prevent uneven dyeing.
[0024] Specific examples of polarizers obtained using laminates include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer coated on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; stretching and dyeing the laminate to make the PVA-based resin layer a polarizer. In this embodiment, stretching typically includes immersing the laminate in an aqueous solution of boric acid to stretch it. Furthermore, stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95°C or higher) before stretching in the aqueous solution of boric acid. The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.
[0025] The thickness of the polarizer is preferably 15 μm or less, more preferably 1 μm to 12 μm, further preferably 3 μm to 12 μm, and particularly preferably 3 μm to 8 μm. When the thickness of the polarizer is within such a range, the desired T PSA / T PWR and T PSA / T OL Furthermore, curling during heating can be effectively suppressed, and good durability of appearance during heating can be obtained.
[0026] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 41.5% to 46.0%, more preferably 43.0% to 46.0%, and even more preferably 44.5% to 46.0%. The degree of polarization of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more.
[0027] B-2.Protective layer As described above, the viewer-side protective layer 12 preferably has a puncture strength of 4.5 kgf / mm to 12 kgf / mm, more preferably 5 kgf / mm to 10 kgf / mm, and further preferably 5.5 kgf / mm to 8 kgf / mm.
[0028] The viewer-side protective layer 12 may be made of any suitable film as long as it satisfies the above-mentioned puncture strength. Representative examples of the film material include cellulose-based resins such as triacetyl cellulose (TAC) and (meth)acrylic resins. In this specification, "(meth)acrylic" means acrylic and / or methacrylic.
[0029] The retardation layer-attached polarizing plate is typically arranged on the viewing side of an image display device, as described later, and the protective layer 12 is arranged on the viewing side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary. In addition, the protective layer 12 may be subjected to treatment for improving visibility when viewed through polarized sunglasses (typically, imparting an (elliptical) polarization function or imparting an ultra-high phase difference) as necessary. By performing such treatment, excellent visibility can be achieved even when the display screen is viewed through polarized lenses such as polarized sunglasses. Therefore, the retardation layer-attached polarizing plate can be suitably applied to image display devices that can be used outdoors.
[0030] The thickness of the viewer-side protective layer 12 is preferably 10 μm to 40 μm, and more preferably 10 μm to 30 μm. When a surface treatment is applied, the thickness of the viewer-side protective layer 12 includes the thickness of the surface treatment layer.
[0031] The other protective layer 13 is formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the film include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.
[0032] In one embodiment, the separate protective layer 13 is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm, and the retardation Rth(550) in the thickness direction is -10 nm to +10 nm. The thickness of the separate protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 10 μm to 30 μm. As described above, in the embodiment of the present invention, the separate protective layer 13 may preferably be omitted.
[0033] C. First retardation layer and second retardation layer As described above, the first retardation layer 21 and the second retardation layer 22 are each an alignment and solidification layer of a liquid crystal compound (hereinafter, a liquid crystal alignment and solidification layer). For example, the liquid crystal compound may be a liquid crystal compound having a nematic liquid crystal phase (nematic liquid crystal). For example, a liquid crystal polymer or a liquid crystal monomer can be used as such a liquid crystal compound. The mechanism of liquid crystallinity of the liquid crystal compound may be either lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination.
[0034] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a crosslinkable monomer. This is because the liquid crystal monomer can be polymerized or crosslinked (i.e., cured) to fix the alignment state of the liquid crystal monomer. After the liquid crystal monomer is aligned, for example, the liquid crystal monomers can be polymerized or crosslinked with each other to fix the alignment state. Here, a polymer is formed by polymerization, and a three-dimensional network structure is formed by crosslinking, but these are non-liquid crystals. Therefore, the formed retardation layer does not undergo transition to a liquid crystal phase, a glass phase, or a crystalline phase due to temperature changes specific to liquid crystal compounds, for example. As a result, the retardation layer becomes a retardation layer that is not affected by temperature changes and has extremely excellent stability.
[0035] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0036] Any suitable liquid crystal monomer can be used as the liquid crystal monomer. For example, the polymerizable mesogen compounds described in JP-A-2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesogen compounds include BASF's product name LC242, Merck's product name E7, and Wacker-Chem's product name LC-Sillicon-CC3767. For example, nematic liquid crystal monomers are preferred as the liquid crystal monomer.
[0037] The liquid crystal alignment solidified layer can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. In one embodiment, the substrate is any appropriate resin film, and the liquid crystal alignment solidified layer (first retardation layer 21) formed on the substrate can be transferred to the surface of the polarizing plate 10 via the first adhesive layer 31. Similarly, the liquid crystal alignment solidified layer (second retardation layer 22) formed on the substrate can be transferred to the surface of the first retardation layer 21 via the second adhesive layer 32.
[0038] As the above-mentioned alignment treatment, any suitable alignment treatment can be adopted. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any suitable conditions can be adopted according to the purpose.
[0039] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.
[0040] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is a polymerizable monomer or a crosslinkable monomer, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or a crosslinking treatment.
[0041] Specific examples of the liquid crystal compound and details of the method for forming the alignment fixing layer are described in Japanese Patent Application Laid-Open No. 2006-163343. The description of the said publication is incorporated herein by reference.
[0042] Typically, the first retardation layer and the second retardation layer each exhibit a refractive index characteristic of nx > ny = nz. Note that "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range not impairing the effects of the present invention, ny > nz or ny < nz may occur.
[0043] As described above, either the first retardation layer 21 or the second retardation layer 22 can function as a λ / 2 plate, and the other can function as a λ / 4 plate. Here, a case where the first retardation layer 21 can function as a λ / 2 plate and the second retardation layer 22 can function as a λ / 4 plate will be described, but these may be reversed. The thickness of the first retardation layer 21 can be adjusted so as to obtain a desired in-plane retardation of the λ / 2 plate, and can be, for example, 1.5 μm to 2.5 μm. The thickness of the second retardation layer 22 can be adjusted so as to obtain a desired in-plane retardation of the λ / 4 plate, and can be, for example, 0.5 μm to 1.5 μm. As described above, the in-plane retardation Re(550) of the first retardation layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and further preferably 250 nm to 280 nm. The in-plane retardation Re(550) of the second retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and further preferably 130 nm to 160 nm, as described above. The angle between the slow axis of the first retardation layer 21 and the absorption axis of the polarizer 10 is preferably 10° to 20°, more preferably 12° to 18°, and further preferably about 15°, as described above. The angle between the slow axis of the second retardation layer 22 and the absorption axis of the polarizer 10 is preferably 70° to 80°, more preferably 72° to 78°, and further preferably about 75°, as described above. With this configuration, it is possible to obtain characteristics close to ideal reverse wavelength dispersion characteristics, and as a result, it is possible to realize very excellent antireflection characteristics.
[0044] The first retardation layer and the second retardation layer each have an Nz coefficient of preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, when the obtained retardation layer-attached polarizing plate is used in an image display device, a very excellent reflection hue can be achieved.
[0045] The first retardation layer and the second retardation layer may each exhibit an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value changes very little depending on the wavelength of the measurement light.
[0046] As described above, the first retardation layer and the second retardation layer may be replaced with a single retardation layer that exhibits reverse dispersion wavelength characteristics and functions as a λ / 4 plate. In this case, the in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and even more preferably 130 nm to 160 nm; Re(450) / Re(550) is preferably 0.8 to 0.95. Furthermore, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°. Furthermore, in this case, preferably, another retardation layer (so-called positive C plate) whose refractive index characteristics show the relationship nz>nx=ny may be provided on the opposite side of the retardation layer from the polarizer.
[0047] D.Adhesive layer The first adhesive layer 31 and the second adhesive layer 32 are collectively described as an adhesive layer. The first adhesive layer and the second adhesive layer may have the same configuration or may have different configurations. Any appropriate adhesive may be adopted as the adhesive constituting the adhesive layer. Representative examples of the adhesive include active energy ray curable adhesives. Examples of the active energy ray curable adhesives include ultraviolet ray curable adhesives and electron beam curable adhesives. In addition, from the viewpoint of the curing mechanism, examples of the active energy ray curable adhesives include radical curable adhesives, cationic curable adhesives, anionic curable adhesives, and hybrids of radical curable adhesives and cationic curable adhesives. Representative examples of the radical curable ultraviolet ray curable adhesives may be used. This is because they are highly versatile and the properties (configuration) can be easily adjusted.
[0048] The adhesive typically contains a curing component and a photopolymerization initiator. Typical examples of the curing component include monomers and / or oligomers having functional groups such as (meth)acrylate groups and (meth)acrylamide groups. Specific examples of the curing component include tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, EO-modified diglycerin tetraacrylate, γ-butyrolactone acrylate, acryloylmorpholine, unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, N-methylpyrrolidone, hydroxyethylacrylamide, N-methylolacrylamide, N-methoxymethylacrylamide, and N-ethoxymethylacrylamide. These curing components may be used alone or in combination of two or more.
[0049] Preferably, the adhesive contains a curing component having a heterocycle. Examples of the curing component having a heterocycle include acryloylmorpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, and N-methylpyrrolidone. More preferred curing components are unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone and acryloylmorpholine, and particularly preferred curing components are acryloylmorpholine. The curing component having a heterocycle may be contained in the adhesive at a ratio of preferably 50 parts by weight or more, more preferably 60 parts by weight or more, and even more preferably 70 to 95 parts by weight, relative to 100 parts by weight of the curing component (the total of the curing component and the oligomer component when an oligomer component is present, as described below). The acryloylmorpholine may be contained in the adhesive at a ratio of preferably 5 to 60 parts by weight, more preferably 10 to 50 parts by weight, relative to 100 parts by weight of the curing component (the total of the curing component and the oligomer component when an oligomer component is present).
[0050] The adhesive may further contain an oligomer component in addition to the above-mentioned curing component. By using the oligomer component, the viscosity of the adhesive before curing can be reduced and the operability can be improved. A representative example of the oligomer component is a (meth)acrylic oligomer. Examples of (meth)acrylic monomers constituting the (meth)acrylic oligomer include (meth)acrylic acid (carbon number 1 to 20) alkyl esters, cycloalkyl (meth)acrylates (e.g., cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, etc.), aralkyl (meth)acrylates (e.g., benzyl (meth)acrylate, etc.), polycyclic (meth)acrylates (e.g., 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, etc.), hydroxyl group-containing (meth)acrylic acid esters (e.g., hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropylmethyl-butyl (meth)methacrylate, etc.), alkoxy group- or phenoxy group-containing (meth)acrylic acid esters (e.g., hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropylmethyl-butyl (meth)methacrylate, etc.), and the like. ) acrylic acid esters (2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, etc.), epoxy group-containing (meth)acrylic acid esters (for example, glycidyl (meth)acrylate, etc.), halogen-containing (meth)acrylic acid esters (for example, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethylethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, etc.), alkylaminoalkyl (meth)acrylates (for example, dimethylaminoethyl (meth)acrylate, etc.).Specific examples of (meth)acrylic acid (C1 to C20) alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate. These (meth)acrylates may be used alone or in combination of two or more kinds.
[0051] As the photopolymerization initiator, a photopolymerization initiator well known in the art can be used in an amount well known in the art, and therefore detailed description thereof will be omitted.
[0052] The thickness of the adhesive layer (after the adhesive is cured) is preferably 0.1 μm to 3.0 μm. If the adhesive layer has such a thickness, the above-mentioned desired thickness T WP And the bending index may be easy to achieve.
[0053] Details of the adhesive are described in, for example, JP 2018-017996 A. The disclosure of this publication is incorporated herein by reference.
[0054] E. Adhesive layer The pressure-sensitive adhesive layer preferably has a storage modulus at 25° C. of 1.0×10 4 Pa~1.0×10 6 Pa, more preferably 1.0×10 4 Pa~1.0×10 5 When the storage modulus of the pressure-sensitive adhesive layer is within this range, the thickness T WPThe synergistic effect of this and the effect of optimizing the bending index can improve the bending properties of the retardation layer-attached polarizing plate.
[0055] The creep amount ΔCr of the adhesive layer at 70°C is, for example, 65 μm or less, and may be 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, or even 15 μm or less. The lower limit of the creep amount ΔCr is, for example, 0.5 μm. If the creep amount is within such a range, the foldability of the retardation layer-attached polarizing plate can be improved, as in the case of the storage elastic modulus. The creep value can be measured, for example, by the following procedure: A load of 500 gf is applied vertically downward to the adhesive layer attached to a stainless steel test plate at a joint surface of 20 mm long x 20 mm wide, with the test plate fixed. The creep amount (displacement amount) of the adhesive layer relative to the test plate is measured at each time point 100 seconds and 3600 seconds after the load is started to be applied, and the Cr 100 and Cr 3600 The measured Cr 100 and Cr 3600 From the formula ΔCr = Cr 3600 -Cr 100 The creep amount ΔCr can be calculated by the following equation.
[0056] Any suitable structure may be adopted as the adhesive constituting the adhesive layer. Specific examples of the adhesive constituting the adhesive layer include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of the monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, and the like, an adhesive having desired properties according to the purpose can be prepared. The base resin of the adhesive may be used alone or in combination of two or more. From the viewpoints of transparency, processability, durability, and the like, an acrylic adhesive (acrylic adhesive composition) is preferred. The acrylic adhesive composition typically contains a (meth)acrylic polymer as a main component. The (meth)acrylic polymer may be contained in the adhesive composition at a ratio of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more of the solid content of the adhesive composition. The (meth)acrylic polymer contains alkyl (meth)acrylate as a monomer unit as a main component. Incidentally, (meth)acrylate refers to acrylate and / or methacrylate. The alkyl (meth)acrylate may be contained in the monomer components forming the (meth)acrylic polymer at a ratio of preferably 80% by weight or more, more preferably 90% by weight or more. Examples of the alkyl group of the alkyl (meth)acrylate include linear or branched alkyl groups having 1 to 18 carbon atoms. The average number of carbon atoms in the alkyl group is preferably 3 to 9, more preferably 3 to 6. A preferred alkyl (meth)acrylate is butyl acrylate. Examples of monomers (copolymerizable monomers) constituting the (meth)acrylic polymer include, in addition to alkyl (meth)acrylates, carboxyl group-containing monomers, hydroxyl group-containing monomers, amide group-containing monomers, aromatic ring-containing (meth)acrylates, and heterocyclic ring-containing vinyl monomers. Representative examples of the copolymerizable monomers include acrylic acid, 4-hydroxybutyl acrylate, phenoxyethyl acrylate, and N-vinyl-2-pyrrolidone.The acrylic adhesive composition may preferably contain a silane coupling agent and / or a crosslinking agent. Examples of the silane coupling agent include an epoxy group-containing silane coupling agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent. Furthermore, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. Details of the adhesive layer or the acrylic adhesive composition are described in, for example, JP 2006-183022 A, JP 2015-199942 A, JP 2018-053114 A, JP 2016-190996 A, and WO 2018 / 008712 A, and the descriptions in these publications are incorporated herein by reference.
[0057] The thickness of the pressure-sensitive adhesive layer is preferably 5 μm to 30 μm, and more preferably 10 μm to 20 μm.
[0058] F. Image display device The retardation layer-attached polarizing plate described in the above items A to E can be applied to an image display device. Therefore, an image display device including a retardation layer-attached polarizing plate is also included in the embodiment of the present invention. The image display device typically includes an image display cell and a retardation layer-attached polarizing plate attached to the image display cell via an adhesive layer. Representative examples of the image display device include a liquid crystal display device and an electroluminescence (EL) display device (e.g., an organic EL display device, an inorganic EL display device). In one embodiment, the image display device is an organic EL display device. In one embodiment, the image display device has a curved shape (substantially a curved display screen) and / or can be bent or folded. In such an image display device, the effect of the retardation layer-attached polarizing plate according to the embodiment of the present invention becomes remarkable. EXAMPLES
[0059] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified. (1) Thickness The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics, product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). (2) Puncture strength The film constituting the viewing side protective layer used in the examples and comparative examples was placed on a compression tester (manufactured by Kato Tech, product name "NDG5", needle penetration force measurement specifications) equipped with a needle, and pierced at a piercing speed of 0.1 cm / sec until the film cracked in a room temperature (23°C ± 3°C) environment, and the maximum load at the time of cracking was divided by the dent depth (mm) to obtain the piercing strength. The piercing strength of three sample pieces was measured, and the average value was used as the evaluation value. The needle used had a tip diameter of 1 mmφ and a radius of 0.5R. (3) Bending test The polarizing plates with retardation layers obtained in the examples and comparative examples were cut into a size of 100 mm x 20 mm to be used as measurement samples. Here, the cut was made so that the absorption axis direction of the polarizer was 135° counterclockwise with respect to the long side direction. This measurement sample was subjected to a continuous folding test using a bending tester (manufactured by Yuasa System Equipment Co., Ltd., product name "CL09 Type D01"). The folding speed was 60 rpm, the folding amplitude was 20 mm, and the folding curvature radius was 0.5 mm. The folding was performed at room temperature with the viewing side protective layer facing outward. Every 50,000 folding times, appearance defects (air bubbles in the adhesive layer, cracks in the polarizer) were observed, and folding was stopped when appearance defects were observed. The number of folding times was set to an upper limit of 300,000 times.
[0060] [Example 1] 1. Preparation of Polarizing Plates As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained. Furthermore, a TAC film (Konica Minolta, Inc., "KC2UA", thickness 25 μm) was attached as a protective substrate (protective layer) to the surface of the obtained polarizer (the surface opposite to the resin substrate) via an ultraviolet-curable adhesive. Specifically, the curable adhesive was applied so that the total thickness was about 1.0 μm, and the films were attached using a rolling machine. Thereafter, the adhesive was cured by irradiating it with UV light from the TAC film side. Next, the resin substrate was peeled off to obtain a polarizing plate having a TAC film (protective layer) / polarizer configuration. The piercing strength of the TAC film was 6.17 kgf / mm.
[0061] 2. Preparation of the first retardation layer and the second retardation layer A liquid crystal composition (coating liquid) was prepared by dissolving 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: product name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: product name "Irgacure 907") in 40 g of toluene. [ka] The surface of a polyethylene terephthalate (PET) film (thickness 38 μm) was rubbed with a rubbing cloth and subjected to an alignment treatment. The direction of the alignment treatment was set to be 15° from the viewing side with respect to the direction of the absorption axis of the polarizer when it was attached to the polarizing plate. The above liquid crystal coating liquid was applied to this alignment-treated surface with a bar coater, and the liquid crystal compound was aligned by heating and drying at 90°C for 2 minutes. The liquid crystal layer thus formed was then irradiated with 1 mJ / cm using a metal halide lamp. 2 The liquid crystal layer was cured by irradiating the liquid crystal with light, forming a liquid crystal alignment solidified layer A on the PET film. The liquid crystal alignment solidified layer A had a thickness of 2 μm and an in-plane retardation Re(550) of 270 nm. Furthermore, the liquid crystal alignment solidified layer A had a refractive index distribution of nx>ny=nz. The liquid crystal alignment solidified layer A was used as a first retardation layer. A liquid crystal alignment solidified layer B was formed on a PET film in the same manner as above, except that the coating thickness was changed and the alignment treatment direction was set to a 75° direction relative to the absorption axis direction of the polarizer when viewed from the viewing side. The liquid crystal alignment solidified layer B had a thickness of 1 μm and an in-plane retardation Re(550) of 140 nm. Furthermore, the liquid crystal alignment solidified layer B had a refractive index distribution of nx>ny=nz. The liquid crystal alignment solidified layer B was used as a second retardation layer.
[0062] 3. Preparation of polarizing plate with retardation layer The liquid crystal alignment solidified layer A (first retardation layer) and the liquid crystal alignment solidified layer B (second retardation layer) obtained in the above 2 were transferred in this order onto the polarizer surface of the polarizing plate obtained in the above 1. At this time, the transfer (lamination) was performed so that the angle between the absorption axis of the polarizer and the slow axis of the alignment solidified layer A was 15°, and the angle between the absorption axis of the polarizer and the slow axis of the alignment solidified layer B was 75°. In addition, each transfer (lamination) was performed via an ultraviolet-curing adhesive (thickness 1.0 μm). Finally, an acrylic adhesive layer (thickness: 15 μm) was disposed on the surface of the alignment solidified layer B (second retardation layer). In this way, a retardation layer-attached polarizing plate having a configuration of protective layer / adhesive / polarizer / first adhesive layer / first retardation layer / second adhesive layer / second retardation layer / adhesive layer was obtained. The thickness of the obtained retardation layer-attached polarizing plate was 51 μm, and T WP The thickness was 36 μm (0.036 mm). The obtained polarizing plate with a retardation layer was subjected to the evaluation in the above (3). The results are shown in Table 1.
[0063] [Example 2] A retardation layer (a single retardation layer that exhibits inverse dispersion wavelength dependency and can function as a λ / 4 plate) and another retardation layer (a positive C plate) were prepared as follows. 55 parts of the compound represented by formula (II), 25 parts of the compound represented by formula (III), and 20 parts of the compound represented by formula (IV) were added to 400 parts of cyclopentanone (CPN), and then the mixture was heated to 60°C and stirred to dissolve. After dissolution was confirmed, the mixture was returned to room temperature, and 3 parts of Irgacure 907 (manufactured by BASF Japan Ltd.), 0.2 parts of Megafac F-554 (manufactured by DIC Corporation), and 0.1 parts of p-methoxyphenol (MEHQ) were added and further stirred to obtain a solution. The solution was transparent and uniform. The obtained solution was filtered through a 0.20 μm membrane filter to obtain a polymerizable composition. On the other hand, the polyimide solution for the alignment film was applied to a glass substrate having a thickness of 0.7 mm by spin coating, dried at 100°C for 10 minutes, and then baked at 200°C for 60 minutes to obtain a coating film. The obtained coating film was subjected to rubbing treatment to form an alignment film. The rubbing treatment was performed using a commercially available rubbing device. The polymerizable composition obtained above was applied to a substrate (substantially an alignment film) by spin coating, and dried at 100° C. for 2 minutes. After the obtained coating film was cooled to room temperature, it was irradiated with 30 mW / cm 2 of a high-pressure mercury lamp. 2 The liquid crystal alignment layer was irradiated with ultraviolet light at an intensity of 1000 nm for 30 seconds to obtain a liquid crystal alignment layer. The liquid crystal alignment layer had a thickness of 2.8 μm and an in-plane retardation Re(550) of 130 nm. The liquid crystal alignment layer had a Re(450) / Re(550) of 0.851 and showed reverse dispersion wavelength characteristics. This liquid crystal alignment layer was used as a retardation layer. [ka] [ka]
[0064] A liquid crystal coating liquid was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (I) (the numbers 65 and 35 in the formula indicate the mol% of the monomer unit, and are conveniently represented as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. Then, the coating liquid was applied to a substrate film (norbornene-based resin film: manufactured by Nippon Zeon Co., Ltd., trade name "Zeonex") using a bar coater, and then the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. This liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, thereby forming a liquid crystal alignment solidified layer (positive C plate, thickness 3 μm) that becomes another retardation layer on the substrate. This layer had Re(590) of 0 nm and Rth(590) of -100 nm, and exhibited refractive index characteristics of nz>nx=ny. [ka]
[0065] A polarizing plate with a retardation layer having a structure of protective layer / adhesive / polarizer / first adhesive layer / retardation layer / second adhesive layer / positive C plate / adhesive layer was obtained in the same manner as in Example 1, except that the liquid crystal alignment solidified layer obtained above was used. The thickness of the obtained polarizing plate with a retardation layer was 52 μm, and T WP The thickness was 37 μm (0.037 mm). The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0066] [Comparative Example 1] A polarizing plate with a retardation layer having a configuration of protective layer / adhesive / polarizer / first adhesive layer / first retardation layer / second adhesive layer / second retardation layer / pressure-sensitive adhesive layer was obtained in the same manner as in Example 1, except that a cycloolefin resin (COP) film ("ZEONORFILM" manufactured by ZEON Corporation, thickness 25 μm) was used as the viewing-side protective layer instead of the TAC film. The piercing strength of the COP film was 1.19 kgf / mm. The thickness of the obtained polarizing plate with a retardation layer was 53 μm, and the T WP The thickness was 38 μm (0.038 mm). The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0067] [Comparative Example 2] A retardation layer (a single retardation layer that exhibits reverse dispersion wavelength dependency and can function as a λ / 4 plate) was prepared as follows. Polymerization was carried out using a batch polymerization apparatus consisting of two vertical stirring reactors equipped with a stirring blade and a reflux condenser. Bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane (BPFM) (30.31 parts by mass (0.047 mol) synthesized by the method described in JP 2015-25111 A), isosorbide (ISB, manufactured by Rocket Fleuret) (39.94 parts by mass (0.273 mol), spiroglycol (SPG, manufactured by Mitsubishi Gas Chemical Co., Ltd.) (30.20 parts by mass (0.099 mol), diphenyl carbonate (DPC, manufactured by Mitsubishi Chemical Co., Ltd.) (69.67 parts by mass (0.325 mol), and calcium acetate monohydrate (7.88 × 10) as a catalyst were used. -4 Part of mass (4.47×10 -6mol) was charged. After the inside of the reactor was purged with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 220 ° C., and while controlling to maintain this temperature, the pressure was simultaneously reduced, and 90 minutes after reaching 220 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 110 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 240 ° C. and the pressure was set to 20 kPa in 40 minutes. Thereafter, the polymerization was allowed to proceed while further reducing the pressure until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the polyester carbonate produced was extruded into water, and the strands were cut to obtain pellets. The ratio of structural units derived from each monomer of this resin was BPFM / ISB / SPG / DPC=21.5 / 39.4 / 30.0 / 9.1% by mass. The obtained pellets were vacuum-dried at 100°C for 6 hours or more, and then a film-forming device equipped with a single-screw extruder (manufactured by Isuzu Chemical Engineering Co., Ltd., screw diameter 25 mm, cylinder set temperature: 250°C), a T-die (width 300 mm, set temperature: 220°C), a chill roll (set temperature: 120 to 130°C) and a winder was used to produce a long unstretched film with a length of 3 m, width of 200 mm and thickness of 100 μm. This long unstretched film was stretched at a stretching temperature of Tg (139°C) to obtain a retardation film with a thickness of 37 μm. The obtained retardation film exhibited refractive index characteristics of nx>ny=nz, Re(550) was 145 nm, and Re(450) / Re(550) was 0.85.
[0068] A polarizing plate with a retardation layer having a structure of protective layer / adhesive / polarizer / adhesive layer / retardation layer (retardation film) / adhesive layer / positive C plate / adhesive layer was obtained in the same manner as in Example 2, except that the retardation film obtained above was used as the retardation layer, and the retardation film was attached to the polarizer via a pressure-sensitive adhesive layer (thickness 5 μm) instead of an adhesive layer. The thickness of the obtained polarizing plate with a retardation layer was 92 μm, and T WP The thickness was 77 μm (0.077 mm). The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0069] [Comparative Example 3] A retardation layer (a single retardation layer that exhibits reverse dispersion wavelength dependency and can function as a λ / 4 plate) was prepared as follows. 26.2 parts by mass of isosorbide (ISB), 100.5 parts by mass of 9,9-[4-(2-hydroxyethoxy)phenyl]fluorene (BHEPF), 10.7 parts by mass of 1,4-cyclohexanedimethanol (1,4-CHDM), 105.1 parts by mass of diphenyl carbonate (DPC), and 0.591 parts by mass of cesium carbonate (0.2% by mass aqueous solution) as a catalyst were charged into a reaction vessel, and in a nitrogen atmosphere, the heat medium temperature of the reaction vessel was raised to 150°C as the first stage of the reaction, and the raw materials were dissolved (about 15 minutes) while stirring as necessary. Next, the pressure in the reaction vessel was increased from normal pressure to 13.3 kPa, and the heat medium temperature of the reaction vessel was raised to 190°C in one hour, while the generated phenol was extracted from the reaction vessel. After the temperature in the reaction vessel was kept at 190°C for 15 minutes, the pressure in the reaction vessel was set to 6.67kPa, the heat transfer medium temperature in the reaction vessel was raised to 230°C in 15 minutes, and the generated phenol was extracted outside the reaction vessel. As the stirring torque of the stirrer increased, the temperature was raised to 250°C in 8 minutes, and the pressure in the reaction vessel was reduced to 0.200kPa or less to remove the generated phenol. After reaching a predetermined stirring torque, the reaction was terminated, and the reaction product was extruded into water and pelletized to obtain a polycarbonate resin with BHEPF / ISB / 1,4-CHDM=47.4 mol% / 37.1 mol% / 15.5 mol%. The obtained polycarbonate resin was vacuum-dried at 80°C for 5 hours, and then a polycarbonate resin film having a thickness of 120μm was produced using a film-forming device equipped with a single-screw extruder (manufactured by Isuzu Chemical Engineering Co., Ltd., screw diameter 25mm, cylinder set temperature: 220°C), a T-die (width 200mm, set temperature: 220°C), a chill roll (set temperature: 120-130°C) and a winder. This resin film was stretched at a stretching temperature of Tg (139°C) to obtain a retardation film having a thickness of 47μm. The obtained retardation film showed a refractive index characteristic of nx>ny=nz, Re(550) was 145nm, and Re(450) / Re(550) was 0.85.
[0070] A polarizing plate with a retardation layer having a structure of protective layer / adhesive / polarizer / adhesive layer / retardation layer (retardation film) / adhesive layer / positive C plate / adhesive layer was obtained in the same manner as in Comparative Example 1, except that the retardation film obtained above was used as a retardation layer, and the retardation film was attached to a polarizer via a pressure-sensitive adhesive layer (thickness 5 μm) instead of an adhesive layer. The thickness of the obtained polarizing plate with a retardation layer was 102 μm, and T WP The thickness was 87 μm (0.087 mm). The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0071] [Comparative Example 4] A polarizing plate was prepared as follows. A polyvinyl alcohol resin film with an average degree of polymerization of 2,400, a degree of saponification of 99.9 mol%, and a thickness of 30 μm was prepared. The polyvinyl alcohol film was stretched 2.4 times in the conveying direction while swelling by immersing it in a swelling bath (water bath) at 20 ° C for 30 seconds between rolls with different peripheral speed ratios (swelling step), and then stretched 3.7 times in the conveying direction based on the original polyvinyl alcohol film (polyvinyl alcohol film that was not stretched at all in the conveying direction) while immersing it in a dyeing bath (aqueous solution with an iodine concentration of 0.03 wt % and a potassium iodide concentration of 0.3 wt %) at 30 ° C so that the single-piece transmittance after the final stretching becomes a desired value (dyeing step). The immersion time at this time was about 60 seconds. Next, the dyed polyvinyl alcohol film was stretched in the conveying direction to 4.2 times the original polyvinyl alcohol film while immersed in a 40°C crosslinking bath (aqueous solution with a boric acid concentration of 3.0% by weight and a potassium iodide concentration of 3.0% by weight) (crosslinking step). Furthermore, the obtained polyvinyl alcohol film was immersed in a 64°C stretching bath (aqueous solution with a boric acid concentration of 4.0% by weight and a potassium iodide concentration of 5.0% by weight) for 50 seconds to be stretched in the conveying direction to 6.0 times the original polyvinyl alcohol film (stretching step), and then immersed in a 20°C cleaning bath (aqueous solution with a potassium iodide concentration of 3.0% by weight) for 5 seconds (cleaning step). The washed polyvinyl alcohol film was dried at 30°C for 2 minutes to prepare a polarizer (thickness 12 μm). The adhesive used was an aqueous solution containing an acetoacetyl group-containing polyvinyl alcohol resin (average polymerization degree 1,200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylolmelamine in a weight ratio of 3: 1. Using this adhesive, a TAC film with a thickness of 25 μm was attached to both sides of the polarizer obtained above to obtain a polarizing plate.
[0072] A retardation layer-attached polarizing plate having a structure of protective layer / adhesive / polarizer / adhesive / protective layer / first adhesive layer / first retardation layer / second adhesive layer / second retardation layer / adhesive layer was obtained in the same manner as in Example 1, except that the polarizing plate obtained above was used and the thickness of the adhesive layer was changed to 30 μm. The thickness of the obtained retardation layer-attached polarizing plate was 98 μm, and TWP The thickness was 68 μm (0.068 mm). The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0073] [Comparative Example 5] A polarizing plate with a retardation layer having a structure of protective layer / adhesive / polarizer / adhesive / protective layer / adhesive layer / retardation layer (retardation film) / adhesive layer / positive C plate / adhesive layer was obtained in the same manner as in Comparative Example 3, except that the polarizing plate of Comparative Example 4 was used. The thickness of the obtained polarizing plate with a retardation layer was 140 μm, and T WP The thickness was 125 μm (0.125 mm). The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0074] In Table 1, for example, "50k" means that no appearance defect was observed after 50,000 bending cycles, but appearance defect was observed after 100,000 bending cycles. Also, for example, "less than 50k" means that appearance defect was observed after 50,000 bending cycles.
[0075] [Table 1]
[0076] [evaluation] As is clear from Table 1, according to the embodiments of the present invention, by optimizing the bending index, it is possible to obtain a polarizing plate with a retardation layer having excellent foldability and suppressing appearance defects even in severe bending tests. [Industrial Applicability]
[0077] The retardation layer-attached polarizing plate of the present invention is suitably used as a circular polarizing plate for liquid crystal displays, organic EL displays, and inorganic EL displays. [Explanation of symbols]
[0078] 10 Polarizing plate 11 Polarizer 12 Protective layer 21 First retardation layer 22 Second retardation layer 31 First adhesive layer 32 Second adhesive layer 40 Adhesive layer 100 Polarizing plate with retardation layer
Claims
[Claim 1] a polarizing plate including a polarizer and a protective layer on at least the viewing side of the polarizer; a retardation layer having a circular polarization function or an elliptically polarizing function, the retardation layer being provided on the side opposite to the viewing side of the polarizing plate; a pressure-sensitive adhesive layer provided on the opposite side of the retardation layer to the polarizing plate, The thickness T from the viewing side protective layer to the retardation layer WP is 0.06 mm or less, A polarizing plate with a retardation layer, having a bending index represented by the following formula of 150 or more: Bending index = puncture strength of the visible side protective layer (kgf / mm) / T WP (mm).
Citation Information
Patent Citations
Retardation film and optical device using the same
JP3325560B2